Optimal time for the addition of non-corticosteroid immunosuppressants in myasthenia gravis: a single-center retrospective study in China - Jiaojiao Ma; Dan Chen; Fangfang Yi; Jie Song; Sushan Luo; Huahua Zhong; Jianying Xi; Zongtai Wu; Zunbo Li; Chongbo Zhao (Frontiers in Neurology)
IntroductionPatients with myasthenia gravis (MG) display strong treatment heterogeneity. Recent studies have indicated that low-dose steroids or immunosuppressants are effective. However, factors affecting the add-on of non-corticosteroid immunosuppressants to corticosteroids remain unknown.MethodConsecutive patients with MG were retrospectively reviewed from May 15, 2015, to December 29, 2020. We included one group of patients with steroid treatment alone and another group who transitioned to non-steroid immunosuppressant therapy. Clinical features of the included patients were analyzed. Univariate and multivariate Cox regression models were used to identify potential influential factors.ResultsA total of 107 patients with MG were analyzed, including 66 receiving corticosteroid treatment alone and 41 who subsequently also received non-corticosteroid immunosuppressant therapy. Eight potential factors were primarily selected in univariate analysis (Ps < 0.1). Achieving minimal symptom expression (MSE) within 6 months (HR: 4.424, 95%CI: 2.102–11.865), body mass index (BMI) (HR: 0.385, 95% CI: 0.186–0.797), quantitative MG (QMG) bulbar muscle score (HR: 1.553, 95% CI: 1.140–2.118), disease duration (HR: 0.987, 95% CI: 0.977–0.997) and relapse (HR: 2.638, 95% CI: 1.031–6.750) were finally identified as potential influencing factors.DiscussionWe found multifactorial clinical factors were highly associated with the add-on of non-steroid immunosuppressants after steroid treatment in patients with MG. Achieving MSE within 6 months, BMI, QMG bulbar muscle score at baseline before steroid treatment, disease duration, and disease relapse may represent crucial influencing factors, which should be considered to improve the long-term prognosis for patients with MG in future studies and practice.